THE INFLUENCE OF CARD SORT LEARNING MEDIA ON THE ACTIVE LEARNING OF IPS STUDENTS IN CLASS VII SMP AL-IKLAS LUBUKLIGGAU - Agus Susilo, Isbandiyah, Citra Wulandari, (Universitas Labuhanbatu, 2024)
The aim of this research is to determine the effect of active social learning on class VII students at Al-Ikhlas middle school Lubuklinggau after the card sort learning media was implemented. This research method uses the experimen method. The data celloction technique used was a questioner. The population in the study were students at Al-Ikhlas middle school Lubuklinggau, which consisted of 3 classes, namely A,B,C totaling 63. The sample in this study used 2 classes, namely class B as the experimental class, totaling 21 and control class totaling 21 students. sData analysis techniques determine the average value and standard deviation, normality test, homogeneity test. The result of this research can be seen from the t-test, namely tcount (32,9) > ttable (2,02), meaning that Ho is rejected and ha is accepted. This shows that the learning activity of experimental class students is not the same as the control class (( ), so it can be concluded that there is an influence of the use of card sort media on the social studies learning activity of class VII students at Al-Ikhlas middle school Lubuklinggau.